Crimes without Punishment: An Update on Violence against Women and Impunity in Guatemala - Musalo, Karen (Social justice, 2013)
The article reports on violence against women and discusses impunity for crimes in Guatemala. Topics discussed include prevalence and patterns of violence against women in Guatemala, barriers for effective implementation of the laws on gender violence, and institution of a monitoring program for evaluating the performance of public officials in carrying out obligations to apply the laws on gender violence. It also mentions gender discrimination as the main cause for violence against women.